THE IMPACT OF INFORMATION QUALITY AND SYSTEM QUALITY ON USER SATISFACTION IN WEB-BASED INFORMATION SYSTEM (Study on the Employees of Bank Rakyat Indonesia Malang) - Rechardilla Ardyanti Kumala (Fakultas Ilmu Administrasi Universitas Brawijaya, 2015)
The aim in this research are to analyze and explain the influence of information and system quality on BRINETS user satisfaction partially and simultaneously in Bank Rakyat Indonesia Malang. Research that is used to test the hypothesis is explanatory research that performed using quantitative method. Data collection is conducted using questionnaire, interview and documentation techniques. Variable that used in this research are Information Quality, System Quality and User Satisfaction. Data analysis is conducted using Descriptive and Inferencial Statistic Methods including Multiple Regression Analysis. The result are that information quality has significant impact with user satisfaction. System Quality has significant impact with user satisfaction. Information quality and system quality has significant impact with user satisfaction.However, the user satisfaction that employees felt not too big because some of them found that BRINETS still not good. This is because many obstacles that occur in BRINETS. Generally, system and information quality of BRINETS is good enough but, some employees believe that it is not good even worse. Keywords: web based information system, information quality, system quality, user satisfaction, BRINETS (BRI Integrated Network and Information System).